Parametric Optimization of Abrasive Water Jet Cutting on AA 5083 through Multiobjective Teaching-Learning Method - R. Meenakshi Reddy; K. Logesh; S. V. Alagarsamy; A. Nagaraj; Rishabh Chaturvedi; Mylavarapu Kalyan Ram; A. H. Seikh; M. H. Siddique; Beruk Hailu (Advances in Materials Science and Engineering)
The industrial sector is seeing an increase in the development of new technologies on a daily basis. Manufacturing advancements have resulted in low-intensity, inadequate outputs from cutting materials. The application of engineering materials requires cutting to produce the desired shapes and sizes. The material’s fundamental attributes are altered and utilised to improve machinability. Due to its significant benefits over traditional cutting processes, abrasive water jet cutting (AWJC) is now the most popular nonconventional machining for attaining the best cutting of any material. Because of its highly pressurised water power, the substance can quickly be separated from some properties by the use of a small pin with various kinds of abrasives. Due to the time-consuming process of cutting materials, determining optimal cutting conditions for the multiobjective criteria examined is a tough issue in techniques needing large resources. The operational parameters of the abrasive water jet cutting system must be changed in this article to achieve the lowest possible surface roughness while also attaining the maximum possible material removal rate. The abrasive water jet cutting method was utilised in this investigation to see how effectively the AA5083 aluminium alloy could be sliced. Water pressure, transverse speed, stand-off distance, and abrasive flow rate are some of the major cutting parameters that may be adjusted such that the output values such as material removal rate and surface roughness are at their optimal levels.